2009
DOI: 10.1038/tpj.2009.23
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate metabolizer: increased side effects in psychoactive drug therapy. The key to cost-effectiveness of pretreatment CYP2D6 screening?

Abstract: The cytochrome P450 2D6 (CYP2D6) isoenzyme metabolizes about 25% of clinically used drugs. The impact of CYP2D6 metabolizer status on therapeutic outcome was assessed in 365 psychiatric in-patients treated with neuroleptics or antidepressants. Length of hospitalization and response onset were prolonged for patients receiving CYP2D6 drugs. Intermediate metabolizers (IMs) receiving CYP2D6 doses above the population median had more side effects after 4 weeks than extensive metabolizers with abovemedian doses (9/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 28 publications
(41 reference statements)
0
18
1
6
Order By: Relevance
“…The sum of the CYP2D6 alleles is considered as the semiquantitative gene dose. This method classifies gene dose 0.5-1 (CYP2D6def/red, CYP2D6red/red, and CYP2D6*1/def) as IM phenotype as exemplified by Laika et al 31 and Steimer et al 32 However, based on the present and previous studies, collectively considering CYP2D6*1/def, CYP2D6red/red, and CYP2D6def/red genotypes as encoding IM phenotype can lead to loss of important phenotypical information within this group, as the former genotype clearly outnumbers the genotypes with 2 variant alleles. Therefore, in evaluating impact of CYP2D6 phenotype on pharmacokinetics and clinical effect, we suggest a separation of IMs in 2 groups: (1) genotypes with 1 fully functional and 1 nonfunctional variant allele and (2) genotypes with 2 variant alleles.…”
Section: Discussionmentioning
confidence: 99%
“…The sum of the CYP2D6 alleles is considered as the semiquantitative gene dose. This method classifies gene dose 0.5-1 (CYP2D6def/red, CYP2D6red/red, and CYP2D6*1/def) as IM phenotype as exemplified by Laika et al 31 and Steimer et al 32 However, based on the present and previous studies, collectively considering CYP2D6*1/def, CYP2D6red/red, and CYP2D6def/red genotypes as encoding IM phenotype can lead to loss of important phenotypical information within this group, as the former genotype clearly outnumbers the genotypes with 2 variant alleles. Therefore, in evaluating impact of CYP2D6 phenotype on pharmacokinetics and clinical effect, we suggest a separation of IMs in 2 groups: (1) genotypes with 1 fully functional and 1 nonfunctional variant allele and (2) genotypes with 2 variant alleles.…”
Section: Discussionmentioning
confidence: 99%
“…25 Across the genetic variants of CYP2D6, the prescribed doses for poor metabolizers typically need to be 30% to 40% lower to achieve similar steady-state serum concentrations as ultrarapid metabolizers. 26 Similarly, agents that induce or inhibit CYP3A4 have been reported to increase or decrease aripiprazole clearance, 24 however, which that genetic variant of CYP3A4 can cause an increase or decrease in aripiprazole clearance is unclear.…”
mentioning
confidence: 99%
“…24,33,34 Today, most evidence exists for an influence of CYP polymorphisms on motor adverse effects of APs, such as TD. Although some studies reported negative findings, [35][36][37][38] there is growing evidence that CYP2D6 PMs are at higher risk of developing acute EPSs 39,40 or TD [41][42][43] (see reviews 13,44,45 ). Some studies have also associated CYP1A2*1F with TD, 42,46 but other studies and a meta-analysis have yielded negative findings.…”
mentioning
confidence: 99%